Leptomeningeal dissemination of anaplastic medullary cone astrocytoma: an unexpected findings in a patient with leptomeningeal enhancement and clinical history of multiple myeloma - Daffini, Linda; Pagani, Francesca; Cominelli, Manuela; Lodoli, Giovanni; Tironi, Andrea; Poliani, Pietro Luigi (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2021)
We report a challenging autopsy case with an insidious clinical presentation with diffuse lepto- and pachymeningeal enhancement in a context of a complex clinical history. Clinical features, neuroradiological and anamnestic data were consistent with central nervous system (CNS) dissemination of a previously known lambda restricted multiple myeloma. Autoptic findings allowed to discard this hypothesis. Unexpectedly, CNS sampling revealed an atypical glial cell proliferation within the sacral meningeal layers. No primary intraparenchymal CNS glial lesion was found. Findings supported the final diagnosis of anaplastic astrocytoma IDH1-wild type of the medullary cone with diffuse leptomeningeal and cerebrospinal fluid (CSF) dissemination. This occurrence represents an extremely rare condition itself, further complicated by the clinical history of the patient that led to formulate the most probable diagnosis of localization of the primary known disease. This autopsy case underlines that patients previously diagnosed with a primary tumor are not only at risk of recurrences or progression of the original disease, but they must be always accurately checked for eventual onset of a second tumor, including rare conditions such as gliomatosis.